The magmetic properties anh charge-ordering state in La1-xCaxMnO3 (x=0.46; 0.50) compounds - Sinh, Nguyen Huy; Tuan, Nguyen Anh; Mai, Vu Thanh; Quang, Pham Hong; Son, Nguyen Tuan (VNU Journal of Science: Mathematics - Physics, 2005)
Abstract